2016
DOI: 10.1080/15438627.2016.1234472
|View full text |Cite
|
Sign up to set email alerts
|

Validation and calibration of HeadCount, a self-report measure for quantifying heading exposure in soccer players

Abstract: The long-term effects of repetitive head impacts due to heading are an area of increasing concern and exposure must be accurately measured; however, the validity of self-report of cumulative soccer heading is not known. In order to validate HeadCount, a two week recall questionnaire, the number of player reported headers was compared to the number of headers observed by trained raters for a men's and a women's collegiate soccer teams during an entire season of competitive play using Spearman's correlations and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 40 publications
2
33
0
Order By: Relevance
“…Individual player self-report has also been used to estimate the frequency of heading impacts in youth, collegiate and amateur players. [75][76][77] Player self-report has been (very recently) shown to overestimate actual observed counts. 71 In that small study of 12 youth females over a 20-game season, the authors concluded 'all players overestimated the number of headers compared with game video.…”
Section: Youthmentioning
confidence: 99%
“…Individual player self-report has also been used to estimate the frequency of heading impacts in youth, collegiate and amateur players. [75][76][77] Player self-report has been (very recently) shown to overestimate actual observed counts. 71 In that small study of 12 youth females over a 20-game season, the authors concluded 'all players overestimated the number of headers compared with game video.…”
Section: Youthmentioning
confidence: 99%
“…In this study, we examined whether self-reported ( 11 , 28 , 32 , 33 ) unintentional head impacts or heading in a 2-week period explained variation in performance on a battery of NP tests.…”
Section: Introductionmentioning
confidence: 99%
“…61 Lipton et al further created self-report measures to estimate heading in soccer, known as the HeadCount or HeadCount-2w, which have predicted acute functional brain alterations in active soccer players. 36,38,62,63 Continued development and validation of RHI exposure measures across the different sports will greatly facilitate research on the short-and long-term neurologic effects of RHI. Exposure to RHI: The Importance of When Not all individuals exposed to RHI develop CTE and individual exposure differences may influence the pathological development of CTE.…”
Section: In Vivo Evidencementioning
confidence: 99%